A secure logistics model based on blockchain. Issue 7 (9th August 2021) - Yi, Haibo
ABSTRACT: Modern services of logistics has developed and expanded rapidly in China. The information of package delivery is managed by the logistics enterprises. Thus, while enjoying the modern services of logistics, consumers face the threats of personal privacy disclosure. In order to address such challenges in modern services of logistics, we present techniques to exploit blockchain to secure logistics for protecting personal privacy. The main contribution is that we propose alogistics blockchain model. We implement the logistics blockchain on the decentralised and distributed platform, which shows that it is efficient and secure.